Politeness in dialogic pragmatics and in the pragmatics of dialogue: a case study of TV series - Scholte, Tom; Fomina, Tatiana A.; Polyakov, Oleg G.; Rakedzon, Tzipora (Язык и культура)
Polite language, i.e. use of appropriate words and face-saving strategies in communication, is often assumed to be a norm-centered practice one needs to follow to achieve pragmatic aims. However, it takes more than one to be polite. In cases of politeness there are at least two actors engaged in an interaction with each other and their own experience of the world. Upon such a dialogic pragmatic view of language, proposed in the article, word and utterance meaning is relationally co-authored and coconstructed. It is hypothesized that politeness is a discursive interplay of attitudes and emotions where one's understanding of a word as polite or offensive, pleasant or rude, appropriate or tabooed depends not as much upon the ontological "denotatum" of this word as upon the interaction with another's understanding of the word. This relational approach to language politeness is informed by such schools of epistemology as pragmatism and empiricism, dialogism and constructivism.